Problem Dikotomi Keilmuan dan Reorientasi Kurikulum Lembaga Pendidikan Islam - Ahmad Saefudin (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2017)
Since the 19th century, Islamic educational institutions confronted to modern era full of challenges. If not ready, the Muslim community will be represented as a passive receptor secular paradigm of Western education. Even though, for most observers of Islamic education, secularism that puts sense in the highest position exceeds â€œnaqliâ€ aspect is a